If it's not what You are looking for type in the equation solver your own equation and let us solve it.
u in (-oo:+oo)
(7/2)*u-1 = (-3/5)*u-(1/2) // - (-3/5)*u-(1/2)
(7/2)*u-((-3/5)*u)+1/2-1 = 0
(7/2)*u+(3/5)*u+1/2-1 = 0
41/10*u-1/2 = 0 // + 1/2
41/10*u = 1/2 // : 41/10
u = 1/2/41/10
u = 5/41
u = 5/41
| 4y=-8(2)+12 | | 7(2-3m)=-7 | | 6(10+7d)=480 | | 8x-7=x | | 5(-2+3m)=-175 | | 5(6n+1)=185 | | 2(-8-5w)=-76 | | y=-(-2)+6 | | 2(7w-2)=94 | | 7(5a+2)=14 | | 2(-1+4k)=86 | | y=-(0)+6 | | 7(10+4x)=378 | | 7(5w-9)=147 | | 3log(2x)+log(x)=1.5 | | 26.54-x=0.05(50-x) | | -15x-3x=-7x+45 | | 4x+-4+6x+49=5(2x+9) | | 5(3b+8)=100 | | y=-(2)+6 | | 3(6k+4)=-96 | | 3(4b-9)=57 | | 7(6+3x)=294 | | .5x-3x+5=0 | | 3ln(2x)+ln(x)=1.5 | | 2(5b-5)=30 | | 7(8+d)=70 | | 2(-1a-6)=-20 | | 6(5-7b)=156 | | 14+x=16.1 | | x^2-8x+8x+(-1x^2)=0 | | 3-x=1+x |